Cardiopulmonary Phenotypes of Post Acute Sequelae of Severe Acute Respiratory Syndrome Coronavirus 2: A Narrative Review. Issue 3 (20th October 2021) - Khan, Muhammad H.; Becker, Richard C.
Abstract : The acute effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are well known; however, the long-term cardiopulmonary effects are less well characterized. The phenotypic expression of acute infection is heterogeneous, ranging from a complete absence of symptoms to shock, multisystem organ failure, and death. Patients with severe or critical coronavirus disease (COVID-19) who survive their initial illness can require a prolonged period of recovery lasting weeks to months. This specific patient group is part of a larger and even more heterogeneous group of patients who initially experience mild-to-moderate symptoms that fail to resolve over time. Collectively, patients recovering from severe or critical COVID-19 and those who continue to experience symptoms following a lower acuity infection are considered to have Post Acute Sequalae of SARS-CoV-2 infection (PASC). Using prognostic factors like myocardial infarction, myocarditis, pulmonary embolism, acute respiratory distress syndrome, need for mechanical ventilation or extracorporeal membrane oxygenation, and advanced pharmaceutical therapies that primarily occur or are instituted in the acute phase of illness one can begin to develop a taxonomy or corpus of PASC in its varied forms.